Co-contamination by heavy metal and organic pollutant alters impacts of genotypic richness on soil nutrients - Huang, Lin; Yao, Si-Mei; Jin, Yu; Xue, Wei; Yu, Fei-Hai (Frontiers in Plant Science, 2023)
Co-contamination by heavy metal and organic pollutant may negatively influence plant performance, and increasing the number of genotypes for a plant population may reduce this negative effect. To test this hypothesis, we constructed experimental populations of Hydrocotyle vulgaris consisting of single, four or eight genotypes in soils contaminated by cadmium, cypermethrin or both. Biomass, leaf area and stem internode length of H. vulgaris were significantly lower in the soil contaminated by cypermethrin and by both cadmium and cypermethrin than in the soil contaminated by cadmium only. A reverse pattern was found for specific internode length and specific leaf area. In general, genotypic richness or its interaction with soil contamination did not influence plant growth or morphology. However, soil nutrients varied in response to soil contamination and genotypic richness. Moreover, plant population growth was positively correlated to soil total nitrogen, but negatively correlated to total potassium and organic matter. We conclude that co-contamination by cadmium and cypermethrin may suppress the growth of H. vulgaris population compared to contamination by cadmium only, but genotypic richness may play little role in regulating these effects.